21. EVALUATING HARD TISSUE AND SOFT TISSUE CHANGES AFTER TREATMENT OF CLASS II ANGLE MALOCCLUSION WITH MBT BRACKET SYSTEM AT CAN THO THE UNIVERSITY OF MEDICAL AND FACIAL DENTAL (Vietnam Journal of Community Medicine, 2023)
Background: Analysis of cephalometric films plays an important role in diagnosis and treatmentplanning. Film measurements were used to classify malocclusion and to compare post-treatmentchange.Objective: To evaluate the results of hard and soft tissue changes after treatment of Class II Anglemalocclusion with the MBT bracket system at the Department of Odonto-Stomatology, Can ThoUniversity of Medicine and Pharmacy.Materials and methods: The study was conducted on 31 patients with Class II Angle malocclusionat the Department of Odonto-Stomatology, Can Tho University of Medicine and Pharmacy. Conductorthopedic treatment of class II Angle malocclusion. Evaluation of changes in bones, teeth, and softtissue on cephalometric radiographs and all X-ray films will be analyzed by specialized softwarewith copyright V-ceph 6.0. Compare the indicators on the film before and after treatment.Results: The index of the angle SNA, ANB, OP-SN, and SN-GoGn changed before and aftertreatment, with statistical significance (p
Keywords: Cephalometric, class II malocclusion, soft tissue, bone tissue.